Tourism potential of Lake Tudakul in Navoi region - Shakhrizoda, Kholmirzaeva; Sadriddinovna, Amriddinova Rayhona (Journal of Higher Education and Academic Advancement, 2024)
This article describes the possibilities for the development of water tourism at the Tudakul Lake, located in the Kyzyltepa district of the Navoi region republic of Uzbekistan